Using Polymer Conformation to Control Architecture in Semiconducting Polymer/Viral Capsid Assemblies - Ng, Benny C. (2011)
Cowpea Chlorotic Mottle Virus is a single-stranded RNA plant virus with a diameter of 28 nm. The proteins comprising the capsid of this virus can be purified and reassembled either by themselves to form hollow structures, or with polyanions like double-stranded DNA or single-stranded RNA. Depending on pH and ionic strength, a diverse range of structures and shapes can form. The work presented here focuses on using these proteins to encapsulate a fluorescent polyanionic semiconducting polymer, MPS-PPV (poly-2-methoxy-5-propyloxy sulfonate phenylene vinlyene), in order to obtain optically active virus-like particles. After encapsulation, fluorescence from MPS-PPV shows two distinct peaks, which suggests the polymer may be in two conformations. A combination of TEM, fluorescence anisotropy, and sucrose gradient separation indicate that the blue peak arises from polymer encapsulated into spherical particles, while the redder peak corresponds to polymers contained in rod-like cages. Ionic strength during assembly can be used to tune the propensity to form rods or spheres. The results illustrate the synergy of hybrid synthetic/biological system – polymer conformation drives the structure of this composite material, which in turn modifies the polymer optical properties. This synergy could be useful for the future development of synthetic/biological hybrid materials with designated functionality.